ANALYSIS OF MERGER & ACQUISITION MOTIVES IN INDONESIAN LISTED COMPANIES THROUGH FINANCIAL PERFORMANCE PERSPECTIVE - Josua Tarigan; Alfonsis Claresta; Saarce Elsye Hatane (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2018)
This study aims to analyse the financial performance of Indonesia companies undergoing M&A in the period of 2009-2012 by comparing several accounting ratios from four years before and after M&A. The sample of this study is 136 annual reports, ranged from 2005 until 2016 of non-banking companies in Indonesia Stock Exchange (IDX). The financial performance of the companies was assessed by several ratios, to measure accounting and market measurement simultaneously to fully assess the M&A performance. The mean of these ratios from four years before was being compared to the mean from four years after M&A; using Paired Sample T-Test, Wilcoxon Signed Rank Test and MANOVA. The test done showed that most of the Indonesian companies undergoing M&A are (a) pursuing for growth and financial synergy motives (b) operating synergies objective needs longer time to be achieved, and (c) accounting and market measurement had been in line revealing semi-strong form of market efficiency in Indonesia.Keywords: Merger and Acquisition, Motives, Financial Performance, Market measurement, Indonesia.